SEBUAH SYSTEMATIC LITERATURE REVIEW MENGENAI PENERAPAN ISLAMIC MINFULLNESS PADA KESEHATAN MENTAL - Astutik, Fuji (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Mental health issues are still one of the priority issues that need to be addressed. The high suicide rate in 2023 indicates that the handling of mental health issues is not optimal. This study aims to examine more deeply related to Islamic mindfulness as an effort to overcome mental health problems. The research method used is a systematic literature review. Based on data base from google scholar, crossref and semantic scholar with the help of publish or perish application. The articles accessed were from 2019-2023. The results showed that Islamic mindfulness interventions are effective for solving mental health problems such as anxiety, depression and increasing resilience both in adolescents, adults and the elderly. The conclusion of this study is that mental health problems can be overcome with Islamic mindfulness through intention, muhasabah, repentance, body scan, prayer, tawakal, relaxation and evaluation